Decision Engine to Support the Path to Net Zero - Ibrahim, I.; Aeeneh, S.; Albergo, P.; Appleby, G.; Bhattacharya, M.; Dormer, A.; De Koninck, L.; Eggleston, J.; Hossain, J.; Young, M.; Wallace, M.; Zhang, F.; et al. (2023)
The Australian government released its long-term emissions reduction plans in achieving net zero emissions by 2050. By enabling companies to plan their path to net zero, this project has led first steps in helping them to convert promises into action. The project surveyed current practice in devising and meeting Greenhouse Gas (GHG) reduction targets. The assessment of current GHG footprint in several companies was elicited and analysed. These targets were broken down into the three scopes (i.e., 1, 2, and 3), social and community impacts of their targets and plans, cost, and organisational commitment. Considering three detailed case studies, Sydney Water, AGL Energy, and the Tassal Group, a set of investment alternatives for reducing their GHG emissions were elicited. In the presence of environmental constraints and costs, possible future scenarios were projected. Complementing these studies, the project analysed both socio-political and technical constraints and the resulting options for companies planning their steps towards net zero. Besides the properties of current energy sources, we investigated future developments in renewable resource options, costs and availability. From the annual reports of selective organisations, Sydney Water, AGL, Salvation Army and Monash net zero, seven socio-political themes were extracted, whose priorities would influence their path to net zero. On this basis the project evolved the design for a decision support platform in supporting to capture both current GHG footprint, and the development of a plan of any organisation in formulating a schedule of actions to meet its GHG reduction targets. This fast-track project sets a platform towards the next steps. These steps include to transform the platform from a design and proof of concept (currently capturing energy usage, sources, scopes, assets, and time periods), to a full production version that can accelerate path to net zero for Australia.